2020
DOI: 10.1111/nph.16740
|View full text |Cite
|
Sign up to set email alerts
|

Bulbous perennials precisely detect the length of winter and adjust flowering dates

Abstract: Summary In order to identify the most relevant environmental parameters that regulate flowering time of bulbous perennials, first flowering dates of 329 taxa over 33 yr are correlated with monthly and daily mean values of 16 environmental parameters (such as insolation, precipitation, temperature, soil water content, etc.) spanning at least 1 yr back from flowering. A machine learning algorithm is deployed to identify the best explanatory parameters because the problem is strongly prone to overfitting for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
1
19
2
Order By: Relevance
“…In mountains, there can be great spatial variability in plant responses because of topographic heterogeneity (Inouye, 2008; Klimešová et al., 2013; Scherrer & Körner, 2010), increasing the importance not only of macroclimatic conditions, but also microclimatic conditions, for herb growth (Winkler et al., 2016). Flowering time is also linked to snow cover variation, and the daily difference in snow depth as compared to the mean value for the same calendar day can be the greatest predictor for bulbous perennials (Jánosi et al., 2020).…”
Section: Perennating Organs In a Changing Climatementioning
confidence: 99%
“…In mountains, there can be great spatial variability in plant responses because of topographic heterogeneity (Inouye, 2008; Klimešová et al., 2013; Scherrer & Körner, 2010), increasing the importance not only of macroclimatic conditions, but also microclimatic conditions, for herb growth (Winkler et al., 2016). Flowering time is also linked to snow cover variation, and the daily difference in snow depth as compared to the mean value for the same calendar day can be the greatest predictor for bulbous perennials (Jánosi et al., 2020).…”
Section: Perennating Organs In a Changing Climatementioning
confidence: 99%
“…The differences in the three key parameters (meteorological factors, length of the time window, N , and the number of sample sizes, S ) involved in the data‐preparation stage of the binary classification model between different species might provide an important reference for exploring the driving factors affecting plant phenology in natural conditions. Meteorological factors as parameters can help us to infer the most relevant climatic factors regulating plant phenology in different climatic zones (Janosi et al, 2020). A single meteorological factor or a combination of meteorological factors was selected as an input feature of the model, and the results showed that temperature was the most effective meteorological factor (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Plant phenology was already investigated in Hungary, in studies focusing on leaf phenology, flowering time, or other aspects of the phenological cycle [9,29,[55][56][57][58][59][60][61]. In a study looking at the flowering of six mixed herbaceous and woody species between 1951 and 2000, the date of flowering advanced by 1.9-4.4 days/decade in four out of the six species [60].…”
Section: Spring Plant Phenology In Central Europementioning
confidence: 99%